IEEE INFOCOM 2007 - 26th IEEE International Conference on Computer Communications 2007
DOI: 10.1109/infcom.2007.319
|View full text |Cite
|
Sign up to set email alerts
|

A Receiver-Coordinated Approach for Throughput Aggregation in High Bandwidth Multicast

Abstract: In application-level high bandwidth multicast (HBM), physical links can be shared by multiple long-lived unicast flows. We identify several data transfer patterns which can cause suboptimal bandwidth usage of narrow links and which have not been clearly identified in previous solutions for application-level HBM.We propose a distributed solution to avoid these problematic patterns, with which end systems are coordinated and each is responsible to forward a bounded amount of data. Consequently, the outgoing traf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…Recent work by Tsang et al [16] identified a number of data transfer patterns that cause suboptimal bandwidth usage of bottleneck links. They proposed a solution which involves topologically close receivers to request data in a coordinated way.…”
Section: Related Workmentioning
confidence: 99%
“…Recent work by Tsang et al [16] identified a number of data transfer patterns that cause suboptimal bandwidth usage of bottleneck links. They proposed a solution which involves topologically close receivers to request data in a coordinated way.…”
Section: Related Workmentioning
confidence: 99%
“…Another difficulty in multicasting is the issue of cross-traffic where different multicast sessions interfere with one another due to commonly shared physical network. Tsang et al [9] applies a receiver-coodinated approach to overcome the issue of cross-traffic in multicasting using multicast trees.…”
Section: Related Workmentioning
confidence: 99%